Renal artery Doppler findings in fetuses of mothers with preeclampsia - Şirinoğlu, Hicran; Atakır, Kadir; Emeklioglu, Cagdas Nurettin; Mihmanlı, Veli; Genç, Simten; Bademler, Neslihan (The European Research Journal, 2022)
Objectives: Preeclampsia (PE), which affecting multi-organ systems, is one of the most common causes of feto-maternal morbidity and mortality. The fetal kidney is one of the vulnerable organs in PE caused by sustained vasospasm of the renal arteries. In this study, it was aimed to reveal the changes in the renal vascular bed with renal artery Doppler examinations in fetuses of pregnant women with PE. Methods: Fifty-five pregnant women with PE and 60 healthy pregnant women were included in this prospective study. Multiple pregnancies, those who did not want to participate in the study, and those with other co-morbidities were excluded from the study. Fetal renal artery Doppler studies included renal artery systolic/diastolic (S/D) ratio, pulsatility index (PI) and resistance index (RI) of the control and PE groups, and findings such as week of birth and birth weight were recorded and analyzed statistically. Results: Fetal renal artery PI values were found to be higher in pregnant women with PE compared to the control group (2.93 in the patient group, 2.28 in the control group, p < 0.001). There was no significant difference between RI values and S/D ratios between the two groups. In the preeclampsia group, gestational week and baby weight at birth were significantly lower. Conclusions: Due to preeclampsia, hypoxia occurs in peripheral tissues and organs at the maternal level. Fetal organs are also affected by these hypoxic conditions. Doppler is an extremely useful examination tool in the evaluation of the status of peripheral organs such as the kidney. This study suggests that PE increases the resistance of renal arteries in fetuses of mothers with PE compared to fetuses of mothers without PE, which may contribute critically to kidney disease later in life.